Ethnoscience-Based STEM Learning on Science Process Skills, Learning Interests, and Learning Outcomes of Students at SMAN 1 Girimarto - Fitri Wulansari; Rina Astuti; Annur Indra Kusumadani (Journal of Biology Learning, 2026)
This study aims to analyze the effect of implementing STEM-based learning integrated with ethnoscience on improving science process skills, learning interest, and learning outcomes of students at SMAN 1 Girimarto. This study uses a quantitative approach with a quasi-experimental research type. The research design used is One Shot Case Study, which is a design that only involves one experimental group without a control group. The population in this study were all students in grade XI at SMA Negeri 1 Girimarto. The research sample was 32 students in grade XI D. The sampling technique used purposive sampling. The results of observations of basic science process skills (KPSD) show varying achievements across five main indicators, with patterns that reflect the level of cognitive difficulty of each skill. The overall average score of 73.06 (medium category) indicated that students collectively responded positively to the integration of local wisdom values in science learning, although individual variability remained. The distribution of student learning outcomes shows very encouraging academic achievement with a dominance of good to very good categories, indicating the success of the implementation of ethnoscience-based STEM learning in improving understanding of excretory system concepts. It can be concluded that the implementation of STEM learning based on ethnoscience on the excretory system material has a positive impact on the three aspects of learning studied with varying levels of success.